Grout diffusion model in porous media considering the variation in viscosity with time. (January 2019) - Hou, Fujin; Sun, Keguo; Wu, Qingdong; Xu, Weiping; Ren, Sijia
Grouting engineering is widely used in water plugging for geotechnical engineering. However, grout is usually treated as a Newton fluid and the viscosity is considered unchangeable over time during the grouting design process. This study proposes a grout diffusion model for porous media that considers the variation in viscosity with time. The flow equation is derived for a single smooth tubule. Then, the microequation of Bingham grout flowing in porous media is obtained. Finally, an assembled diffusion model of spheres and cylinders for grouting using a perforated pipe is proposed. A numerical simulation method is used to verify the grout diffusion mode. The research results can guide grouting design and practical grouting engineering in water plugging and reinforcement.